Advances in Multiaxial Fatigue 1993
DOI: 10.1520/stp24800s
|View full text |Cite
|
Sign up to set email alerts
|

In-Phase and Out-of-Phase Axial-Torsional Fatigue Behavior of Haynes 188 Superalloy at 760°C

Abstract: Isothermal, in-phase and out-of-phase axial-torsional fatigue experiments have been conducted at 760°C on uniform gage section, thin-walled tubular specimens of a wrought cobalt-base superalloy, Haynes 188. Test control and data acquisition were accomplished with a minicomputer. Fatigue lives of the in- and out-of-phase axial-torsional fatigue tests have been estimated with four different multiaxial fatigue life prediction models, a majority of which were developed primarily for predicting axial-torsional fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 18 publications
0
27
0
Order By: Relevance
“…Figure 6 shows that Socie's model gives good predictions for proportional loading but unconservative predictions for non‐proportional loading. Kalluri and Bonacuse 18 applied the model for fatigue life prediction to Haynes 188 high‐alloy steel under non‐proportional loading. The results also showed that the predictions were unconservative by up to a factor of four, with the largest deviations occurring for the out‐of‐phase tests.…”
Section: Predictions Of Low‐cycle Fatigue Lifementioning
confidence: 99%
“…Figure 6 shows that Socie's model gives good predictions for proportional loading but unconservative predictions for non‐proportional loading. Kalluri and Bonacuse 18 applied the model for fatigue life prediction to Haynes 188 high‐alloy steel under non‐proportional loading. The results also showed that the predictions were unconservative by up to a factor of four, with the largest deviations occurring for the out‐of‐phase tests.…”
Section: Predictions Of Low‐cycle Fatigue Lifementioning
confidence: 99%
“…6, for notched components, Neuber's analysis has been used to calculate the local stress/strain values at the notch root. The experimental fatigue lives of various materials extracted from the literature [13,[15][16][17][18][19] were plotted in Figs In a study by Fash [19], it was found that using the von Mises criterion, the experimentally predicted life data fall within a factor ranged 1.1-5.33 and with the Lohr-Ellison approach within a range factor of 1.1-7.0. Tipton and Nelson [20] reviewed a number of different methods and found that using the Brown and Miller model, the experimentalpredicted life data fall within a factor ranged 1.1-6.0 and the plastic work approach with a range factor of 1.1-5.0.…”
Section: Resultsmentioning
confidence: 99%
“…5. Specimen geometry: (a) 1045 steel[13], (b) Haynes 188[16], (c) 1020 HR steel[17], (d) high strength steel, t = 2.54 mm[15], (e) AA 2024-T3, t = 2.3 mm[18], (f) AA 7075-T6, t = 2.3 mm[18], (g) 4340 steel, t = 5.1 mm[18] and (h) 1045 steel[19].…”
mentioning
confidence: 99%
“…In order to verify the applicability of parameter n′, 5 kinds of materials, with n′ from 0.0195 to 0.4, were selected from the literature . In addition, to express the effects of additional hardening more intuitively, a strain parameter δε eq , as a temporary substitute for Γ t , is introduced δεeq=normalΔεeq,2normalΔεeq2 where Δ ε' eq is equivalent strain calculated by Manson‐Coffin equation (Equation ) when experimental life N f is given.…”
Section: A New Multi‐axial Fatigue Life Prediction Modelmentioning
confidence: 99%